Optimization Of Human Resources Management In Islamic Banking - Fitra Azkiya Firdiansyah (JPS (Jurnal Perbankan Syariah), 2021)
So far, the rapid development of Islamic banking has not been supported by competent resources according to Islamic principles. The resources contained in Islamic banking so far have been a shift from conventional banking, resulting in the incompetence of these resources in Islamic banking. This study aims to analyze the optimization of human resource management in Islamic banking following Islamic principles. The method in this research is descriptive analysis with a qualitative approach. The analysis uses deductive and inductive techniques from various published literature. The results of the study show that human resources in Islamic banking are not yet optimal. The development and development of available resources must align with the position, training, and development of attitudes and managerial skills instilled with Islamic financial and ethical principles. Islamic banking must cooperate with universities in the coaching process to absorb potential resources with added value and have Islamic-based competencies.